Student Perception Review from Gender: Electronic Moduls of Mathematical Physics - Tanti, Tanti; Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Fitriani, Riska (Jurnal Pendidikan Indonesia, 2022)
The role of technology that continues to develop in the era of globalization, especially in the field of education demands various innovations in the teaching and learning process in order to improve the quality of learning in the world of education. This study aims to examine the differences in the perceptions of students based on gender gender in classes A and B towards the physics-mathematical e-module.This type of research is quantitative and is carried out as surveys. Instrument for collecting data in the form of perception surveys using the likert scale. The data were analysed in statistically descriptive manner (mean, median, mode, frequency and percent) and inferential statistics (hypothesis test: normality test and homogeneity test, and hypothesis test: independent T-test). Sample Techniques is a total sample of 80 gender students from 2 classes. The result of the study is that there is a significant difference between the perception of female students and the level of significance 0.049 and significance level 0.005 for male. As a result, it was concluded that the average perception difference between women and men is lower. Men are more rational in the insertion of something, whereas women are emotive in the insertion of something. The results of this study are expected to contribute to educators in improving the quality of learning in an educational institution.